Influence of Boron Carbide Addition on Performance and Neutron Shielding Ability of Cement Mortar Mix - A J, Satish; P N, Aravind; P V, Hakesh; V, Vignesh; Mini K M, Dr (International Journal of Engineering and Technology, 2018)
Renewable source of energy is the best form of consumable energy that can be harnessed from the earthâ€™s available resources in a sustainable manner. Nuclear energy obtained from nuclear fission reactions from the nuclear reactors is an example of such kind of energy, but deeply requires caution in the handling of operations. Leakage of fast moving high energy neutrons creates harm to both the environment and mankind and hence should be shielded from all available means. One such effort to shield this high energy radiation is by using boron carbide infused cement mortar that can be used for plastering and other similar applications in the construction of nuclear reactors. The strength and performance based characteristics of such type of mortar are studied and improved by adding super-plasticiser and pozzolanic materials like microsilica and metakaolin. Also durability studies like alkalinity, water absorption etc are done to analyse the lifetime of the design mix. EDS and SEM analysis were also performed extensively to study the microstructure of the casted specimen and to analyse the elemental composition cum distribution (by EDS mapping) for the calculation of the neutron attenuation of the specimen mix. Based on these an optimum combination is arrived at for practical applications that has a desirable strength, performance, durability and neutron shielding property.Â Â